Natural history of a mouse model of X-linked myotubular myopathy - Ege Sarikaya; Nesrin Sabha; Jonathan Volpatti; Emanuela Pannia; Nika Maani; Hernan D. Gonorazky; Alper Celik; Yijng Liang; Paula Onofre-Oliveira; James J. Dowling (The Company of Biologists, 2022)
X-linked myotubular myopathy (XLMTM) is a severe monogenetic disorder of the skeletal muscle. It is caused by loss-of-expression/function mutations in the myotubularin (MTM1) gene. Much of what is known about the disease, as well as the treatment strategies, has been uncovered through experimentation in pre-clinical models, particularly the Mtm1 gene knockout mouse line (Mtm1 KO). Despite this understanding, and the identification of potential therapies, much remains to be understood about XLMTM disease pathomechanisms, and about the normal functions of MTM1 in muscle development. To lay the groundwork for addressing these knowledge gaps, we performed a natural history study of Mtm1 KO mice. This included longitudinal comparative analyses of motor phenotype, transcriptome and proteome profiles, muscle structure and targeted molecular pathways. We identified age-associated changes in gene expression, mitochondrial function, myofiber size and key molecular markers, including DNM2. Importantly, some molecular and histopathologic changes preceded overt phenotypic changes, while others, such as triad structural alternations, occurred coincidentally with the presence of severe weakness. In total, this study provides a comprehensive longitudinal evaluation of the murine XLMTM disease process, and thus provides a critical framework for future investigations.